Familial Mesial Temporal Lobe Epilepsy - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2001)
Clinical, genetic, and MR characteristics of 68 patients with familial mesial temporal lobe epilepsy (MTLE) were analysed at the University of Campinas-UNICAMP, Brazil.